Investigation of repeatability and reproducibility of steering characteristics’ measurement - Eriksson, Henrik; Tapper, Linus (My University, 2018)
The study covers an investigation on the repeatability and reproducibility of the steering characteristics test procedure at Volvo Car Corporation (VCC). The steering characteristic test series is performed in six different sub test, responding to different driving scenarios. The project was brought up after VCC performed three series of steering characteristic tests on three different occasions, during similar conditions and with the same car. The results were separated from each other without any explanation. In this study, the causes of spread in results were investigated. Starting by performing three series of tests to clarify if the same set of data results were separated as the ones in the previous three tests. Different sets of result data separated, clarifying that it is not certain which subtests that obtain an uncertainty. Due to time limitations, the three subtests that appeared as "the worst" were selected for further investigation, creating a smaller series containing the selected sub tests. This shorter test set was performed 8 times, 4 times per operator, to collect as much data time could provide. The data was analysed with ANOVA (analysis of variance) to specify spread in data within groups of test set number, operator and turning direction if applicable to test. To observe the influence of external factors, a linear regression model was fitted between each result metric and external factors. The result showed that different tests were affected by different factors, preventing the determination of a certain factor causing the spread in the test procedure. Some tests appeared to be influenced by the calibration of the steering robot, some by the tire conditions and in some cases, no cause of spread could be found. The study has created a good knowledge for further investigation. Even though several important conclusions were made, there is a lot more to dig into and a long list of recommendations in further investigation was achieved.
Keywords: Transport; Farkostteknik; Transport; Vehicle Engineering